Interplay Between the IL-33/ST2 Axis and Bone Marrow ILC2s in Protease Allergen-Induced IL-5-Dependent Eosinophilia - Boberg, Emma; Johansson, Kristina; Malmhäll, Carina; Calvén, Jenny; Weidner, Julie; Rådinger, Madeleine (Frontiers in Immunology, 2020)
Background: Eosinophils develop from CD34+ progenitor cells in the bone marrow under the influence of interleukin (IL)-5. Several cell types produce IL-5, including type 2 innate lymphoid cells (ILC2s). The alarmin cytokine IL-33 is known to activate ILC2s in mucosal tissues, but little is known about IL-33-responsive ILC2s in the bone marrow in allergen-induced airway inflammation. Methods: Wild type (WT) and Rag1 deficient (Rag1-/-) mice, which lack T and B cells, received intranasal doses of papain to induce acute allergic inflammation. In some experiments, mice were pre-treated with anti-IL-5 prior to the papain challenge. Furthermore, recombinant IL-33 was administered to WT mice, Rag1-/- mice, lymphocyte deficient mice (Rag2-/-Il2rg-/-) and to ex vivo whole bone marrow cultures. Bone marrow eosinophils and ILC2s were analyzed by flow cytometry. Eosinophil count was assessed by differential cell count and secreted IL-5 from bone marrow cells by ELISA. Results: Intranasal administration of papain or IL-33 increased the number of mature eosinophils in the bone marrow despite the absence of adaptive immune cells in Rag1-/- mice. In parallel, an increased number of eosinophils was observed in the airways together with elevated levels of Eotaxin-2/CCL24. Bone marrow ILC2s were increased after papain or IL-33 administration, whereas ILC2s was found to be increased at baseline in Rag1-/- mice compared to WT mice. An upregulation of the IL-33 receptor (ST2) expression on bone marrow ILC2s was observed after papain challenge in both Rag1-/- and WT mice which correlated to increased number of bone marrow eosinophilia. Furthermore, an increased number of ST2+ mature eosinophils in the bone marrow was observed after papain challenge, which was further dependent on IL-5. In addition, bone marrow-derived ILC2s from both mouse strains produced large amounts of IL-5 ex vivo after IL-33 stimulation of whole bone marrow cultures. In contrast, IL-33-induced bone marrow and airway eosinophilia were abolished in the absence of ILC2s in Rag2-/-Il2rg-/- mice and no production of IL-5 was detected in IL-33-stimulated bone marrow cultures. Conclusion: These findings establish bone marrow ILC2s and the IL-33/ST2 axis as promising targets for modulation of uncontrolled IL-5 dependent eosinophilic diseases including asthma.